An Indonesian Version of Mental Toughness Index: Testing Psychometric Properties in Athletes and Non-athletes - Miftah Fariz Prima Putra; Kurdi Kurdi; Syahruddin Syahruddin; Sanusi Hasibuan; Albadi Sinulingga; Ilham Kamaruddin; Advendi Kristiyandaru; Mashud Mashud; Imam Hariadi; Tri Setyo Guntoro; Sutoro Sutoro; Evi Sinaga; et al. (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
To date, the mental toughness index (MTI) has been adopted in five different languages ​​but there has been no attempt to adapt and test it in the Indonesian context. On the other hand, the study of mental toughness is experiencing an upward trend but there are problems with the measurement tools used. This research aims to adapt and test the MTI to the Indonesian context by involving athletes and non-athletes as well as gender differences. There were 400 participants, with details of the athlete group = 211 people (Mage = 19.18 years, SD = 1.06, Male = 146, Female = 65), non-athlete group = 189 people (Mage = 23.38 years, SD = 7.11, Male = 144, Female = 45), and based on gender, male = 290 people (Mage = 21.38 years, SD = 5.41), while female = 110 people (Mage = 20.61 years, SD = 5.24). MTI was tested using confirmatory factor analysis (CFA) with maximum likelihood (ML) assisted by the IBM SPSS v.26 and IBM Amos v. programs. 22. Overall, the Indonesian version of MTI (MTIid) shows model fit, namely the values ​​obtained are CFI = .967, TLI = .954, GFI = .966, SRMR = .034, and RMSEA = .069. Eight items in the MTIid have a convergent validity value that is statistically significant (p < 0.001) and the loading factor is very good (λ = .563 to .759), three items are in the excellent category, two items are very good, and three items are good. The internal consistency reliability of the MTIid was excellent (CR = .864; α = .862). MTIid is a valid and reliable measuring tool for measuring aspects of mental toughness, both in groups of athletes and non-athletes and based on gender differences (male and female).